Śrī Sītā kalyāṇam : sampratāya pajaṉai pattati - Nārāyaṇa Cāstiri, Ṭi. Vi (Ē. Kē. Kōpālaṉ, 1981)
Compilation of devotional songs, without musical notation, but with melody (raga) and beat (tala) indications based on an episode from the Ramayana.